Appropriate citation and accuracy of references: read full text before citing (Journal of Patan Academy of Health Sciences, 2022)
Reference accuracy is important for good science. Cited references must be verifiable and accessible to the readers, reviewers, and editors. When the source cannot be found, it raises question of the quality of the manuscript, and also undermine the credibility of the journal (and editors). Almost all the domains of peer-reviewed medical journal literature report errors in referencing and citations which affect indexing, abstracting, and publication metrics. Citation is properly referring to information presented by others’ and provides authenticity to own work by directing readers to the sources.